Evaluation of teaching practice at the University of Limpopo - Mampa, Sekgati Samuel (My University, 2019)
This study reports on the evaluation of Teaching Practice necessary for guiding future best practice of Teaching Practice at the University of Limpopo. The key research question answered in this study was: How is Teaching Practice implemented at the University of Limpopo? The study is embedded within the interpretive paradigm. A qualitative research approach was employed using case study design. Case study design was used in order to explore the research questions that guided the entire study. This enabled the researcher to interact with the participants, immerse himself in the data for better and deeper understanding of the implementation of Teaching Practice. The case study design was also adopted because the researcher had no control over the implementation of Teaching Practice. In other words, the researcher could not manipulate the behaviour of the participants involved in the study. Purposive sampling was used to select knowledgeable and information rich participants comprising of the Director of the School of Education, three Heads of Department, the Teaching Practice coordinator, two academic staff members in the Teaching Practice Unit, the Teaching Practice administrative officer, six academic staff members, six four-year Bachelor of Education in Senior and Further Education and Training students, six Postgraduate Certificate in Education students, four schoolbased mentors in Limpopo, and four school-based mentors in the Mpumalanga Province. Data were captured through document analysis, semi-structured interviews and observations. Inductive analysis was used to analyse data from the documents. Data from semi-structured interviews and observations were analysed thematically. Findings from the documents, semi-structured interviews and observations were used to make recommendations for establishing an Integrated Model of Teaching Practice at the University of Limpopo. The study revealed lack of appropriate policy for Teaching Practice; lack of clear frameworks for the responsibilities of supervisors; student teachers and school-based mentors; lack of school-university partnerships; inadequate training of supervisors and school-based mentors in relation to supervision and assessment of student teachers; lack of a structured programme on the induction of student teachers into schools; poor human, physical and financial resources, and an inappropriate model for Teaching Practice.
Thesis(Ph.D. (Education Curriculum Studies)) -- University of Limpopo, 2019
Keywords: Higher education; Work-integrated learning; Teaching practice; University; Supervisor; Student teacher; School-based mentor; Teaching; Education, Higher -- South Africa -- Limpopo